2022
DOI: 10.1007/s12649-022-01866-y
|View full text |Cite
|
Sign up to set email alerts
|

Pumpkin Peel Valorization Using Green Extraction Technology to Obtain β-Carotene Fortified Mayonnaise

Abstract: This study aimed to recover β-carotene from peels produced as a by-product during the industrial processing of pumpkins using a high-e ciency technology that produces no waste and is harmless to the environment. β-Carotene extraction from pumpkin peel was carried out by maceration and ultrasound-assisted technique, with sun ower oil instead of nhexane as an environment-friendly solvent. In uence of the lecithin:PGPR (polyglycerol polyricinoleate) ratio was studied for microemulsion solvent method on β-carotene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In the case of UAE (127.93 mg/100 g DM) and microemulsion (149.71 mg/100 g DM) with lecithin 0.098 % and polyglycerol 1.902 %, better results appeared than maceration + sunflower oil (99.83 mg/100 g DM) and maceration + n-hexane (125.75 mg/100 g DM). Mayonnaise formed with extracted β-carotene-rich sunflower oil had better sensory quality than control; however, during storage, it was more resistant to oxidation [151] . The apple pomace with ethanol (50:50, v/v) in 1:10 LS ratio was subjected to an ultrasonic bath at 45 ˚C for 45 min for bioactive compounds recovery.…”
Section: Recent Upcycling Approachesmentioning
confidence: 93%
“…In the case of UAE (127.93 mg/100 g DM) and microemulsion (149.71 mg/100 g DM) with lecithin 0.098 % and polyglycerol 1.902 %, better results appeared than maceration + sunflower oil (99.83 mg/100 g DM) and maceration + n-hexane (125.75 mg/100 g DM). Mayonnaise formed with extracted β-carotene-rich sunflower oil had better sensory quality than control; however, during storage, it was more resistant to oxidation [151] . The apple pomace with ethanol (50:50, v/v) in 1:10 LS ratio was subjected to an ultrasonic bath at 45 ˚C for 45 min for bioactive compounds recovery.…”
Section: Recent Upcycling Approachesmentioning
confidence: 93%
“…Gungor and Torun [ 194 ] extracted β-carotene from peels of pumpkins using the maceration, microemulsion, and ultrasound-assisted methods with sunflower oil as the solvent. Data reported that mayonnaise made with sunflower oil rich in β-carotene was well received sensory-wise, and it retained all of its other distinctive qualities.…”
Section: Valorization Of Fruits and Vegetable Waste Into Valuable App...mentioning
confidence: 99%
“…The second strategy stresses the importance of the rational use of products and the reduction in the amount of waste produced [1]. The handling of crop waste is one of the most important problems that the agricultural and food sector has to address nowadays [2]. Processing fruits and vegetables into commercial products generates significant quantities of bulk waste, depending on the species (peels, seeds, shells, skins, leaves, and roots, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pumpkin peel is an excellent source of minerals, protein, fibers, and isoforms of vitamin E. These valuable compounds are associated with the nutritional quality of food, as evidenced by Mala et al [13], who showed that peels are rich in minerals, such as phosphorus and iron, as well as indietary fiber. Kubra Gungor et al [2] used β-carotene from pumpkin peels (C. moschata) generated in the fruit processing industry using high-efficiency technology that produced zero waste and had no harmful effects on the environment. In fact, pumpkin peels contain several compounds that may act as potent antioxidants and antimicrobial agents, or they could be used for their peel powder or extracts for the isolation and characterization of bioactive compounds that could be implemented in the food, nutraceuticals, and pharmaceuticals industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation